Petroleum systems of the Barents shelf. A regional well-based study of the mesozoic - Yankina, Anna (UiT Norges arktiske universitet, 2017)
The entire Barents Sea area has experienced a complex geological evolution. From orogenic processes connected to Caledonian mountain building in Palaeozoic to basin formation related to the opening of the Atlantic Ocean in Paleogene. Uplift and erosion processes (Exhumation) that fined place in Ceinozoic contribute to erosion and redepositing of thick sedimentary sequences over Barents Sea area. Exhumation relates to one of the biggest problems due to petroleum exploration on Barents shelf. It has significant implication on source rock maturation, hydrocarbon potential and reservoir rock properties. Uplift and erosion processes affects basin geometry and burial sedimentary rock properties as well in that way that source rock uplifted to shallow level is not enough mature to produce hydrocarbons. Other consequences connected to exhumation are hydrocarbon redistribution and leakage from traps, decreasing in reservoir quality properties due to compaction processes and porosity reduction. Unfortunately, implication of exhumation processes on petroleum system in the Barents Sea is not fully understood and need more research. Uplift and erosion affects sedimentary rock properties. Log data from wells, especially velocity log, is very sensitive to lithological variation and compaction trends of the rocks. Velocity log data from wells are cruel in executing of analysis of sedimentary basins. It can provide information about burial evolution of the area and changing in temperature gradient. Velocity log data is also important due to recognition of lithological units, overpressure and fluid content in the formations.